Christianity Cultivated Science with and without Methodological Naturalism - Keas, Michael N. (Religions, 2023)
Many people assume ceaseless conflict between natural science and Christianity, but the real conflict has been between scientism and Christianity. Scientism is the view that only the sciences (especially not theology) generate knowledge or rational belief. I show how Christianity generated rational beliefs that contributed to the rise of science. This science-fostering rational belief included rationales for when to practice methodological naturalism, and when to study nature without that restriction. Both practices cultivated science, though in different ways. This historical difference is of enduring value for recent debates about metaphysical naturalism (atheism), creationism, theistic evolution, and intelligent design.